La práctica pedagógica de cinco egresados de licenciatura en Química de la Universidad Distrital, implicada en la enseñanza de la tabla periódica - Ruiz Arandla, María Victoria; Castro Barbosa, Sol Mercedes; Huertas Moya, Oscar Reyned (Revista Científica, 2006)
This article is the result of the observation of the pedagogical practices about of the education of the periodic table, developed by five docent in exercise, UD profesional chemist and four Educative Institutions Distritales. This analysis turns around the categories: curriculum, pedagogical Practices, profesional competition, pedagogical model and periodic Table that they look to investigate, to reveal and to generate the reflection on the education process in the classroom, with the purpose of promoting other projects of investigation that lead as much to the fortification of teachers in formation process as the professionals. The methodological design is based ot the etnography which causes the cultural interpretation at the inner of the interactive communities, allowing to explain the events of the educative process, in where the speech had a fundamental paper, since permitted investigate about the formation of the professional and identify situations that received meaning in the pedagogical practices.